Dental Care of Patients With Dementia: A Survey on Practice Equipment, Training, and Dental Treatment - Schaper, Sophie; Meyer-Rötz, Sinja; Bartels, Claudia; Wiltfang, Jens; Rödig, Tina; Schott, Björn H.; Belz, Michael (Frontiers in Oral Health, 2021)
For patients with dementia, dental care can pose a considerable challenge due to cognitive impairment, behavioral, and psychological symptoms, and (often subsequently) limited autonomous oral care. In this study, we aimed to assess the proficiency of dentists in general practice in the outpatient dental care of these patients. A total of 119 dentists from private practices in Lower Saxony, Germany, participated in this study. Concerning treatment of patients with dementia, they provided details about (1) practice equipment/consultation, (2) training/ expertise, and (3) special circumstances of dental treatment. Participating dentists predominantly reported to use medical aids (e.g., positioning cushions) to improve the treatment situation for patients with dementia. Over two thirds (68.6%) offered consultations in nursing homes, and at the patients’ homes (47.0%). The training rate was remarkably low in the field of gerodontology for dentists and their practice staff (< 10%), however, 54.5% expressed interest in such training. The majority of dentists reportedly adapted their treatment strategy to the needs of patients with dementia (e.g., communication, inclusion of caregivers, time management). Furthermore, most participants adapted dental treatment adequately (e.g., strict indication for tooth extraction, simple design of dental prostheses). In summary, even though training in the field of gerodontology must be considered insufficient, most dentists in this study showed an adequate adaptation of their treatment strategy as well as consideration of dental characteristics in patients with dementia, along with interest in trainings. We conclude that dementia-specific training should be expanded in the field of dentistry, preferably already at university level.